2001
DOI: 10.1128/jvi.75.10.4655-4663.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Immunodeficiency Virus Type 1 Replication in Human T Lymphocytes by Nitric Oxide

Abstract: Addition of nitric oxide (NO) donors to mitogen-activated human immunodeficiency virus type 1 (HIV-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…It is pertinent to note that NO is involved in HIV-1 replication, especially that induced by TNF-α. [1] There might, therefore, be a self perpetuating mechanism wherein HIV replication leads to increased NO production and the latter increases the rate of HIV multiplication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is pertinent to note that NO is involved in HIV-1 replication, especially that induced by TNF-α. [1] There might, therefore, be a self perpetuating mechanism wherein HIV replication leads to increased NO production and the latter increases the rate of HIV multiplication.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is synthesized from L- arginine by a family of three enzyme NO synthase (NOS) proteins, two of which are constitutive (type I and III) and one inducible (type II or iNOS). [2] Citrulline is released by the above reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV induced iNOS expression in infected cells, and NO increased viral LTR (long terminal repeat) expression and replication [32]. In addition to these factors, some cytokines induced by infection, such as TNF-a and IFN-c, stimulated NO production in infected macrophages [33].…”
Section: Nitric Oxide and Viral Infectionsmentioning
confidence: 99%
“…Following up the changes in nitrite/nitrate levels in the human tissues and plasma samples can be an important tool in understanding NO involvement. Although NO is an important mediator of the immune response against microorganisms, NO that is produced during the infectious diseases may be also deleterious, particularly in HIV-1 infection where may contribute to AIDS pathogenesis by enhancing viral replication in lymphocytes (Jimenez et al, 2001) and monocytes (Blond et al, 2000), increasing lymphocyte apoptosis (Mossalayi et al, 1999), and participating in the pathogenesis of AIDS-related dementia complex (Adamson et al, 1996). A study demonstrated impaired iNOS mRNA expression and NO levels in peripheral blood mononuclear cells from HIV-1 infected patients, either in vivo or in vitro HIV-1 infection of normal cells (Cairoli et al, 2008).…”
mentioning
confidence: 99%